The Effects of Sectoral and Economy-Wide Policies on Tobacco Production in the Dominican Republic - Pena, P.; Norton, George W. (Cambridge University Press, 1993)
This study analyses the effects of specific agricultural and exchange rate policies on tobacco production in the Dominican Republic. Direct protection resulting from output and input subsidies and taxes was positive on average from 1966 to 1988, but total protection was negative when exchange rate policies are considered. Tobacco policies were quite volatile and resulted in increasing production in the 1970s but decreasing production in the 1980s. Overall, tobacco production was 4.8 percent less than it would have been had there been no policy interventions. Several reasons are provided for the policies.